Analisis Langkah Model Discovery Learning dan Hasil Belajar Siswa di Sekolah Dasar - Rini Rini (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The purpose of this study is to find learning outcomes in accordance with the theory. This type of research is literature study research. The results showed that there were 5 articles with moderate categorization of the final score of cycle II, and there were 10 articles with high categorization of the final score of cycle II. From 10 articles with high final cycle II grade categorization, it was found that the steps of the discovery learning model in the implementation of learning were: 1) Stimulation: The teacher gave questions, suggested reading books, looked at pictures or told stories according to the material to be studied. 2) Problem Statement: The teacher directs students to identify problems that are relevant to the subject matter, formulate problems to formulate hypotheses. 3) Data Collection: The teacher directs students to collect information by reading books, through direct experiments and asking and observing. 4) Data Processing: The teacher directs students to process data through discussion. 5) Verification: The teacher directs students to practice directly, ask questions and discuss. 6) Generalization: The teacher directs students to make conclusions.